2023
DOI: 10.3390/hydrogen4020025
|View full text |Cite
|
Sign up to set email alerts
|

Natural Gas Pyrolysis in a Liquid Metal Bubble Column Reaction System—Part II: Pyrolysis Experiments and Discussion

Abstract: This contribution presents the results of continued investigations on the production of hydrogen by means of pyrolysis in a liquid metal bubble column reactor, as developed at the Karlsruhe Institute of Technology in recent years. Part I of this contribution described the motivation and the methodology of this study, as well as a significant scale-up, and discussed its results for pure methane pyrolysis. Here in part II, two additional experimental campaigns with methane–ethane mixtures (MEMs) and high-calorif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…This is due to the presence of ethane in natural gas. This effect and potential reasons are described and discussed in more detail in [10]. This experimental result demonstrates that a successful transition from laboratory to industrial scale is possible without reducing the efficiency of the process being developed.…”
Section: Namementioning
confidence: 78%
See 3 more Smart Citations
“…This is due to the presence of ethane in natural gas. This effect and potential reasons are described and discussed in more detail in [10]. This experimental result demonstrates that a successful transition from laboratory to industrial scale is possible without reducing the efficiency of the process being developed.…”
Section: Namementioning
confidence: 78%
“…One important result of these studies is shown in Fig. 2 [10]. The methane to hydrogen yield in experiments using pure methane and high caloric natural gas (molar fraction: 98.2 % methane, 1.71 % ethane, 0.07 % propane, another components 0.02 %) as a process feedstock is compared in the diagram for otherwise similar process conditions.…”
Section: Namementioning
confidence: 99%
See 2 more Smart Citations